A Poverty Analysis Macroeconomic Simulator (PAMS) Linking Household Surveys with Macro-Models - Pereira da Silva, Luiz A.; Essama-Nssah, B.; Samake, Issouf (World Bank, Washington, DC, 2014)
The Poverty Analysis Macroeconomic Simulator (PAMS) is a model that links standard household surveys with macro frameworks. It allows users to assess the effect of macroeconomic policies-in particular, those associated with Poverty Reduction Strategies papers-on sectoral employment and income, the incidence of poverty, and income distribution. PAMS (in Excel) has three interconnected components: (1) A standard aggregate macro-framework that can be taken from any macro-consistency model (for example, RMSM-X, 123) to project GDP, national accounts, the national budget, the BoP, price levels, and so on, in aggregate consistent accounts. (2) A labor market model breaking down labor categories by skill level and economic sectors whose production total is consistent with that of the macro framework. Individuals from the household surveys are grouped in representative groups of households defined by the labor category of the head of the household. For each labor category, labor demand depends on sectoral output and real wages. Wage income levels by economic sector and labor category can thus be determined. In addition, different income tax rates and different levels of budgetary transfers across labor categories can be added to wage income. (3) A model that uses the labor model results for each labor category to simulate the income growth for each individual inside its own group, assumed to be the average of its group. After projecting individual incomes, PAMS calculates the incidence of poverty and the inter-group inequality. PAMS can produce historical or counterfactual simulations of: + Alternative growth scenarios with different assumptions for inflation, fiscal, and current account balances. These simulations allow test tradeoffs within a macro stabilization program. + Different combinations of sectoral growth (agricultural or industrial, tradable or non-tradable goods sectors), within a given aggregate GDP growth rate. + Tax and budgetary transfer policies. For example, PAMS will simulate a baseline macro-scenario for Burkina Faso corresponding to an existing IMF/World Bank-supported program and introduce changes in tax, fiscal, and sectoral growth policies to reduce poverty and inequality more effectively than the base scenario. So, the authors argue that there are several possible "equilibria" in terms of poverty and inequality within the same macro framework.